Pembelajaran Pendidikan Agama Islam Pada Anak Berkebutuhan Khusus - M Maftuhin; A Jauhar Fuad (Journal An-Nafs: Kajian Penelitian Psikologi, 2018)
This paper is propose to explain the planning and learning of Islam Education (PAI) for child with special needed in Special School (SLB) on the level of junior high school (SMPLB). The Planning and Learning have paculiar treatments in comparasion with regular junior high school. The methods are used by lecturing, discusing and practicing methods, and also using teacher’s gestures which depend on the class that must be faced. Hence, there are different learning strategies that must be applied by PAI’s teachers for one to another students. This associate to the physical and psychological condition of the student, with the results that it using personal schooling